Pengaruh Durasi Penekanan dan Ukuran Partikel terhadap Kualitas Pelet Serbuk Gergaji - Simanjuntak, Fajar Agustus; Wisnu, Febrian Kusuma; Telaumbanua, Mareli; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2022)
This study aims to determine the effect of pressing duration and particle size on the pellet characteristics of sawdust. The study was conducted in a factorial completely randomized design using two factors. The first factor is the duration of the suppression which consists of four levels, namely 60, 120, 180, and 240 seconds. The second factor is particle size which consists of 40 mesh (fine), 30 mesh (medium), 20 mesh (coarse), and mixed. Sawdust is taken from a furniture industry in Bandar Lampung, then dried in the sun to a moisture content of about 12%, then sieved. Pellet molding was carried out with a mass of about 3 grams of material using a hydraulic press with a mold diameter of 12 mm. Sawdust is fed into the mould, then pressed by a hydraulic system at a pressure of 2 tons (172 Mpa). Parameters observed included density, moisture content, water absorption, pellet strength, pellet color, ash content and durability index. Each measurement was carried out with three replications. The results showed that the pressing duration and particle size affected the pellet characteristics. Biomass pellet made from sawdust had characteristics such as density of 0.813-0.856 g/cm3, moisture content of 8.19-12.15 %, maximum water absorption of 7.06-9.32 %, drop resistance of 99.41-99.66 %, and ash content of 1.087-2.082 %. Keywords: Density, Durability Index, Duration of Compression, Particle Size, Moisture Content.